The effect of carbohydrate feedings in four-hour swimmers
The fuel processes associated with marathon swimming were assessed. Five swimmers swam for four hours on two occasions. During one swim, swimmers were fed a 6% carbohydrate beverage (Gatorade) every 15 min. In the unfed state, at least 50% of the energy production was derived from fat oxidation. It took between one and half and two hours for the fat metabolism to become the major contributor. The greatest concern for swimmers during marathons is maintaining carbohydrate stores. The carbohydrate feedings in this study spared muscle glycogen, although no difference in performance was observed. Implication. It would be desirable, but may be impractical, to replenish glycogen stores during a marathon swim. When a performance has to be completed with fat metabolism as being a primary source of fuel, it is necessary to train using that source. To do that, it might be necessary to reduce the carbohydrate supply of the swimmer so that training will be aerobic but fueled by fat (because of the low level of carbohydrate). Carbohydrate starving should not be performed very frequently. It would be prudent to limit it to two swims a week unless a more frequent occurrence has been shown to be beneficial.